2013
DOI: 10.1128/genomea.01115-13
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Pigment-Producing Bacterium Pseudogulbenkiania ferrooxidans , Isolated from Loktak Lake

Abstract: The whole genome of a pigment-producing isolate from a lake in northern India, Pseudogulbenkiania ferrooxidans strain EGD-HP2, has been sequenced to study the spectrum of biosynthesis of secondary metabolites. The genome annotation data revealed an operon for violacein, which showed homology with the reported operon of a Chromobacterium sp., and also a quinone cofactor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Being a gut commensal present in the flora of healthy individuals, virtually avirulent enterococci have been used as probiotics to benefit health. Therefore we investigated whether a probiotic E. faecalis strain Symbioflor 1 [ 19 ] can be transduced by phages released from E. faecalis V583ΔABC. As expected, induction of prophages in E. faecalis Symbioflor 1 with 100 μM AI-2 did not lead to plaque formation, confirming that Symbioflor 1 does not contain lytic prophages [ 19 ] ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being a gut commensal present in the flora of healthy individuals, virtually avirulent enterococci have been used as probiotics to benefit health. Therefore we investigated whether a probiotic E. faecalis strain Symbioflor 1 [ 19 ] can be transduced by phages released from E. faecalis V583ΔABC. As expected, induction of prophages in E. faecalis Symbioflor 1 with 100 μM AI-2 did not lead to plaque formation, confirming that Symbioflor 1 does not contain lytic prophages [ 19 ] ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, we could confirm that the polylysogenic transfected E. faecalis Symbioflor 1 harbored prophages 1, 5 and 7 ( Table 1 ). As described previously, all Symbioflor 1 strains contain also pp2 as part of the core genome [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…This search and subsequent analysis using IMG-ABC tools took less than an hour, and has led to the identification of putative DAPG biosynthesis clusters in four betaproteobacteria: a bacterium identified as Pseudogulbenkiania ferrooxidans EGD-HP2 (19) and three members of Chromobacterium genus, Chromobacterium vaccinii MWU205 (20), C. vaccinii MWU328 (20) and Chromobacterium piscinae ND17 (21). The IMG tools for analysis of biogeography and habitat specificity of these isolates indicate that all of them were collected from freshwater environments across the globe (Northeastern India, Northeastern United States of America and Malaysia).…”
Section: New Features and Updatesmentioning
confidence: 99%
“…This draft genome has been deposited at DDBJ/EMBL/ GenBank under the accession no. AVPH00000000 [13].…”
Section: Ncbi Database Submissionmentioning
confidence: 99%
“…1, 2). For example, prior studies reported violacein production in chromobacterium species but [13] reported the same in Pseudogulbenkiania ferroxidans EGD-HP2 (EGD-HP2) via genome annotation in which they reported key genes of enzymes for pigment production and further 3D structure prediction. Violacein pigment producing Chromobacterium species was reported for a various biological activity like Anti-bacterial, Anti-cancerous [14], and Anti-leishmania [15].…”
Section: Introductionmentioning
confidence: 99%